FOLKLORE ARCHIVES – WITNESSES OF THE HISTORY OF ETHNOLOGICAL STUDIES - Eleonora SAVA (Studia Universitatis Babeş-Bolyai. Philologia, 2019)
Folklore archives – witnesses of the history of ethnological studies. This study proposes a rereading of the documents kept in a folklore archive from Romania, with a focus on the methods used by those who drafted and archived these documents. The research demonstrates that, in the absence of testimonies regarding the manner in which fieldwork was conducted, the documents of the archive can provide valuable information on the field research and the vision on folklore of several generations of researchers. Thus, archives of folklore are seen as witnesses of the history of ethnology.